CIDADES SUSTENTÁVEIS: UM ESTUDO SOBRE A CIDADE DE GUARAPUAVA/PR - Viante, Marcelo Fernando (2021)
Cities have been playing an essential role in the development of modern society, especially their importance in social, economic and environmental aspects. In order to study the sustainability of cities, indicators are used to research specific aspects of cities and ensure that good practices are shared. Therefore, the combined study of sustainability concepts, its indicators and the Theory of Stakeholders justify the research question that guides this study: What are the stakeholder assessments in relation to ABNT NBR ISO 37120:2017? The research is a descriptive, qualitative study and uses a quantitative method of support through a case study. The main objective was to analyze the indicators of ABNT NBR ISO 37120:2017 in the city of Guarapuava/PR under the light of the Stakeholders Theory. Data collection was based on documents, direct observation, semi-structured interviews with identified agents, considered primary or secondary stakeholders, and a survey applied to the city's residents. Ten interviews were conducted as well as 345 surveys were answered and validated. After the data collection, content analysis was used as an analysis technique for qualitative data, while Spearman's correlation analysis was used for the quantitative data collected. It is conclude that some indicators such as education, recreation and environment had a positive perception by the interviewed stakeholders. While indicators such as housing and economy received more criticism. Regarding the perception of citizens, it was noted that aspects such as health, safety, education and housing were the variables that had both positive and negative results within the municipality. Such points highlighted by the interviewees, observed within the city and presented by the 34 indicators founded allow us to affirm that Guarapuava is not a sustainable city, although it has made small advances in recent years.